Manganese‐Based Na‐Rich Materials Boost Anionic Redox in High‐Performance Layered Cathodes for Sodium‐Ion Batteries. Issue 27 (10th May 2019) - Zhang, Xiaoyu; Qiao, Yu; Guo, Shaohua; Jiang, Kezhu; Xu, Sheng; Xu, Hang; Wang, Peng; He, Ping; Zhou, Haoshen
Abstract: To improve the energy and power density of Na‐ion batteries, an increasing number of researchers have focused their attention on activation of the anionic redox process. Although several materials have been proposed, few studies have focused on the Na‐rich materials compared with Li‐rich materials. A key aspect is sufficient utilization of anionic species. Herein, a comprehensive study of Mn‐based Na1.2 Mn0.4 Ir0.4 O2 (NMI) O3‐type Na‐rich materials is presented, which involves both cationic and anionic contributions during the redox process. The single‐cation redox step relies on the Mn 3+ /Mn 4+, whereas Ir atoms build a strong covalent bond with O and effectively suppress the O2 release. In situ Raman, ex situ X‐ray photoelectron spectroscopy, and soft‐X‐ray absorption spectroscopy are employed to unequivocally confirm the reversibility of O2 2− species formation and suggest a high degree of anionic reaction in this NMI Na‐rich material. In operando X‐ray diffraction study discloses the asymmetric structure evolution between the initial and subsequent cycles, which also explains the effect of the charge compensation mechanism on the electrochemical performance. The research provides a novel insight on Na‐rich materials and a new perspective in materials design towards future applications. Abstract : Mn‐based Na1.2 Mn0.4 Ir0.4 O2 O3 type Na‐rich material is synthesized, which involves both cationic and anionic contribution during the redox process. The single‐cation redox relies on the Mn 3+ /Mn 4+, whereas Ir atoms effectively suppress the O2 release. The O2 2− species is unequivocally confirmed upon cycling, suggesting a high contribution degree of anionic reaction in the Na‐rich material.